Chemical components of polymerase chain reaction in 18s rRNA for detection of Cryptosporidium from river water samples - Barudin, Mohd Aiman; Md Isa, Muhammad Lokman; Mat Yusof, Afzan (Malaysian Analytical Sciences Society, 2019)
The gene of 18S ribosomal RNA or 18S rRNA is the universal gene function as a general genetic marker for species identification of microorganisms including parasites. Cryptosporidium has distinct 18S rRNA genes along different species within the same genus. In this study, polymerase chain reaction or PCR was used to study chemical components of PCR setup in amplification of 18S rRNA gene of this parasite. Cryptosporidium was collected from river water samples and its presence was confirmed using specific immunofluorescence detection of this parasite. Isolated water containing Cryptosporidium was then subjected to genomic DNA extraction before PCR step. The chemical components of PCR consisting of MgCI2, deoxynucleotide triphosphate (DNTPs), Polymerases, free DNase-water, universal primers and PCR buffer were studied in different volume and concentration. Each chemical component of PCR was optimized differently in yielding the same final volume of 20 μL per each reaction. The value range of chemical components of PCR consisted of MgCI2 (0.1 μM-0.5 μM), dNTPs (50-250 mM), free DNase water (5-10 μL), polymerases (0.2-0.5 U) and universal primers (2-20 μM). The result indicated that 0.2 μM of MgCI2, 100 mM of dNTPs, less than 10 μL of free DNase water, 0.5 U of polymerases and 10 mM of universal primers were the best combination to get better result for molecular identification of 18S rRNA Cryptosporidium. As a conclusion, accurate and proper concentration or volume of each PCR chemical components is essential for molecular identification of 18S rRNA Cryptosporidium gene. In future studies, study on gradient temperature parameters of PCR run can be included to study the chemical nature of amplified genes either in denaturation, annealing or extension steps.